Role of Phosphorylation Coupling Factor in Light-Dependent Proton Translocation by Rhodopseudomonas capsulata Membrane Preparations - Melandri, Bruno A. (1970)
The activity of the light-dependent proton pump (in the absence of phosphorylation substrates) of Rhodopseudomonas capsulata „membrane vesicles,” in contrast to that of chloroplasts, is not appreciably affected by detachment of phosphorylation coupling factor(s). Proton uptake by such „uncoupled” (low phosphorylation activity) preparations is also unaffected by the addition of phosphorylation substrates (ADP + arsenate + Mg(2+)). The H(+) pump of „coupled” preparations, however, is stimulated when all of the substrates are present simultaneously. Oligomycin appears to affect both photophosphorylation and the H(+) pump by interaction with a component of the energy transfer sequence that is distinct from coupling factor. The results obtained suggest that in photosynthetic bacteria light-dependent cyclic electron flow (the driving force for photophosphorylation) is accelerated by active phosphorylation which, in turn, is dependent on the presence of protein coupling factors in the energy-converting membrane.